Sistem Informasi Simpan Pinjam Berbasis Web pada Koperasi Jasa Kawan Sejahtera Fakultas Teknik Universitas Pancasila: Web-Based Savings and Loans Information System at the Jasa Kawan Sejahtera Cooperative, Faculty of Engineering, Pancasila University - Sugeng Riyanto; Eva Rahmawati; Hylenarti Hertyana; Elly Mufida (Fakultas Teknik Universitas Pancasila, 2023)
The process of collecting input data, processing it, storing it, analyzing it, and disseminating it is an information system. The purpose of this research is to develop a system that can support the data processing of cooperative members, member lists, and savings and loan processes so that accurate cooperative data and reports can be generated with data input processes and processed through a computerized database in the form of a web-based savings and loan cooperative processing information system. Faculty of Engineering at Pancasila University case studies on the Jasa Kawan Sejahtera cooperative, so that management activities are optimized. System development tools based on the UML (Unified Modeling Language) architecture are used to build this system, along with the PHP programming language, HTML, and MySQL as the database. Based on the findings of the information system that has been implemented, the top management of savings and loan cooperatives may simply and thoroughly monitor and oversee all management actions.